Molecular communication between Apelin-13 Apelin-36, Elabela, and nitric oxide in gestational diabetes mellitus - Karagoz, Z. K.; Aydin, S.; Ugur, K.; Tigli, A.; Deniz, R.; Baykus, Y.; Aksoy, A. (Verduci Publisher, 2022)
OBJECTIVE: Gestational diabetes mellitus (GDM) is a type of diabetes that affects from 3.8% to 6.9% of pregnancies worldwide, causing significant mortality and unfavorable obstetric outcomes. such as delivery trauma and macrosomia risk. The fundamental processes of this metabolic disorder that first appeared during pregnancy are still unknown. Tissue hormones, particularly adipokines. have aided in understanding the pathophysiology of numerous disorders in recent years. This study aims to determine if Apelin-13 (APLN-13), Apelin-36 (APLN-36). Elabela (ELA), and nitric oxide (NO) molecules have all a part in the pathophysiology of GDM. PATIENTS AND METHODS: The study included 30 pregnant control women and 30 pregnant women who had been diagnosed with GDM in the second trimester and whose body mass index and age were compatible with each other. Blood samples were collected from 60 participants during the second trimester (30 control pregnant women and 30 GDM pregnant women) and postpartum (17 controls vs. 14 GDM). In these blood samples, the amounts of APLN-13, APLN-36, ELA, and NO were studied using the ELISA method. In addition, the participants' glucose, lipid profiles, and other parameters were obtained from the hospital record files. At postpartum, 29 pregnant women (13 control and 16 pregnant women with GDM) dropped out of the study without explanation. RESULTS: In the second trimester and postpartum plasma of mothers with GDM. APLN-13, APLN-36. NO. and ELA molecules were found to be significantly higher (< 0.05). compared to those of the control mothers. while APLN-13, APLN-36. NO values were significantly lower (0.05). While APLN-13. APLN-36, NO amounts in mothers with GDM were positively correlated with glucose amounts. they were negatively correlated with ELA amounts. Similarly, the triglyceride amounts in mothers with GDM were positively correlated with APLN-13, APLN-36 and NO, while they were negatively correlated with the ELA amounts. Due to gestational diabetes, APLN-13, APLN-36, NO. glucose. and triglyceride increased. and ELA decreased. CONCLUSIONS: It is predicted that the glucose increase in GDM is because Apelins reduce glucose transport to erythrocytes by inhibiting the sodium-dependent glucose transporter (SGLT) and that the increase in triglyceride and NO may be associated with high glucose levels in GDM. As a result, we believe that the above-mentioned chemicals may cause GDM Pathology by triggering one another.
Keywords: Apelin-13; Apelin-36; Elabela; Gestational diabetes mellitu; Nitric oxide